2014
DOI: 10.1111/crj.12212
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency chest wall oscillation in prolonged mechanical ventilation patients: a randomized controlled trial

Abstract: In PMV patients, HFCWO was safe, comfortable and effective in facilitating airway hygiene after removal of endotracheal tubes, but had no positive impact on weaning success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…7 Subjects included in the study sample had been intubated for 21 d or more and demonstrated a small improvement in chest radiographs compared with subjects who did not receive HFCWC (P ϭ .02). However, the researchers noted no improvement in weaning success rates, oxygenation, anxiety levels, perceived dyspnea, or ICU stay.…”
Section: Hfcwcmentioning
confidence: 96%
“…7 Subjects included in the study sample had been intubated for 21 d or more and demonstrated a small improvement in chest radiographs compared with subjects who did not receive HFCWC (P ϭ .02). However, the researchers noted no improvement in weaning success rates, oxygenation, anxiety levels, perceived dyspnea, or ICU stay.…”
Section: Hfcwcmentioning
confidence: 96%